(untitled) (Sustainability in Debate, 2014)
The discussions about the theme sustainability have intensified itself in recent times. The concerns about environmental and social questions aggregate itself alongside economic concerns. There was an increase of the companies that communicate the strategies of sustainability through a sustainability reporting. The model of reporting of the Global Reporting Initiative is considered one of most utilized in the international context. This study aims to investigate an evolution of degree of adherence full (GAPIE-GRI) and the degree of effective disclosure (GEE) to the social performance (labor practices and decent work and human rights) of Brazilian companies in the sectors of financial services, energy and public service energy, which published the GRI sustainability report between 2007 to 2009. It was observed that the companies had median results in indices GAPIE-GRI and GEE. The energy sector showed higher rates compared to the financial services industry. There was an evolution in communication and commitment to effective communication of social performance.